Variation of HPMC Concentration on The Stability of The Physical Properties of Peel Off Gel Coffee Arabica (Coffea arabica) Peel: Variasi Konsentrasi HPMC Terhadap Stabilitas Sifat Fisik Masker Gel Peel Off Kulit Buah Kopi Arabika (Coffea arabica) - Mega Karina Putri; Salvia A’isyah Shafira; Beta Ria Erika Marita Dellima (B-Creta Publisher, 2026)
Indonesia is the world’s third-largest producer of coffee, behind Brazil and Vietnam. The content of coffee fruit skin compounds is able to protect the skin from UV rays, slow down the premature aging process and improve microcirculation in the blood. This study sough to ascertain whether differences in HPMC concentration in peel off gel mask formulations of fruit peel extract from arabica coffee (Coffea arabica) affect the requirements of physical properties and physical stability of good preparations, and to determine the optimal formula that meets the physical properties and stability requirements for the development of coffee fruit peel-based cosmeics. The sample was arabica coffee fruit peel powder which was made into a thick extract by maceration extraction method using 96% ethanol solvent. The peel off gel mask is formulated into 3 formulas with concentrations of Formulation 1 (HPMC 2%), Formulation 2 (HPMC 2.5%) and Formulation 3 (HPMC 3%). The three peel off gel mask formulas produced were then compared with their physical properties based on days 0, 7, 14, 21 and 28 with organoleptis testing, homogeneity test, pH test, dispersion test and drying time. The results showed that the peel off gel preparation of arabica coffee fruit peel extract (Coffea arabica) had a brown color with a characteristic smell of coffee and Formulation 1, Formulation 2 and Formulation 3 respectively had a slightly viscous, somewhat viscous and viscous consistency. All three formulas have an average pH of 4.5-5.2, Formulation 1 has the greatest dispersion and drying time values compared to Formulation 2 and Formulation 3.